Impactos da seca na logística de transporte no Amazonas em 2024: desafios de acesso a bens de consumo pela população ribeirinha no entorno da BR - 319 - Souza, Carina Sigmaringa de (Brasil, 2024)
The research entitled: “Impacts of Drought on Transport Logistics in Amazonas in 2024: challenges of access to Consumer Goods by the riverside population around BR-319” analyzes how drought affects transport logistics and, consequently, access to goods essential for residents and users of BR-319. Through a mixed approach, which includes bibliographical and field research, an investigation reveals that the reduction in river levels requires navigation and makes transport more expensive, resulting in significant losses for the population of the region. The data obtained from the respondents highlights the difficulties faced, such as the increase in product costs and the scarcity of food, aggravated by two aspects: the collapse of the bridges connecting BR-319 to Manaus in 2022 and which, as of today, 2024 has not yet was concerted and the evidence of the worst drought in the State of Amazonas in 2024 shows the urgent need for solutions. As a proposal, two alternatives are suggested: The creation of a cooperative of ferries and small boats, made up of community members, to mitigate the social impacts of the drought and guarantee the continuous transport of goods and services. The research not only understands the problem, but also presents viable alternatives that promote adaptation and sustainable development in the Amazon region.As a second alternative, I present the construction of a new bridge connecting the municipalities of Bela – Vista and Manaquiri. The bridge infrastructure would also contribute to the creation of new business and business opportunities, benefiting the local population. It would play an important role in the stability of riverside communities, especially during seasonal climate adversities, such as drought.